Building an E-Book Library. - Zipke, Marcy (Reading Teacher, 2014)
There is a wide range in the educational qualities and overall quality of interactive storybook apps for tablet computers (ebooks). Minimally, ebooks for young children present illustrations on a screen, accompanied by an oral reading of the text. Today's ebooks can also include animation, zooming in and out, musical scores, sound effects, text highlighting, built-in dictionaries, hotspots where the reader clicks to interact with a character or object, foreign language translations, and more. While some ebooks do represent quality children's literature presented in a format that optimizes the affordances of the technology, others more closely resemble cartoons. Therefore, teachers, school librarians, and other school officials need to become educated consumers who carefully consider which ebooks they are buying for young elementary students. This article gives guidelines for evaluating the educational potential of ebooks, and makes specific suggestions for resources on how to find high-quality apps for beginning readers.